Reforms of Pension System in Lithuania - Gylys, Povilas (Ekonomika, 2004)
Lithuania, like other Central European countries, undergoes a deep reform of the old age security system. The reform takes place in a controversial cognitive environment. The controversy is between methodological individualism and methodological holism as peculiar worldviews. The two world outlooks provide different reform perceptions and scenarios.